2015
DOI: 10.1186/s12955-015-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of diabetes knowledge, attitudes, self-management, and quality of life: a cross-sectional study with an Australian sample

Abstract: BackgroundQuality of life (QoL) is an important aspect of wellbeing for people with chronic conditions like type 2 diabetes, making it a noteworthy outcome. Knowledge about diabetes, attitudes, and self-management of diabetes are key factors that might directly or indirectly impact QoL. However, little is known about the inter-relationships between diabetes knowledge, attitudes, self-management and QoL among people with type 2 diabetes mellitus (T2DM). The aim of this study was to examine a model describing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 50 publications
7
70
3
10
Order By: Relevance
“…24 A research performed in Criciuma-SC found that the higher the positive attitude of confrontation of the disease, greater the QL in the physical domain (p<0.05), 10 consistent with this research. However, for the elderly have better attitude related to treatment, the family support is essential.…”
supporting
confidence: 83%
“…24 A research performed in Criciuma-SC found that the higher the positive attitude of confrontation of the disease, greater the QL in the physical domain (p<0.05), 10 consistent with this research. However, for the elderly have better attitude related to treatment, the family support is essential.…”
supporting
confidence: 83%
“…A qualitative study by Ong, Chua, and Ng () suggested that poor diabetes‐related knowledge was reported to have a strong relationship with a low level of education and older adults. Subsequently, research has indicated a significant association ( p < 0.01) between poor diabetic knowledge and poor glycaemic control (Kueh, Morris, Borkoles, & Shee, ; Shams, Amjad, Seetlani, & Ahmed, ; Worku, Abebe, & Wassie, ). Furthermore, three qualitative studies indicated that that poor diabetes‐related knowledge leads to poor adherence to diabetes self‐management steps, such as following medication protocols and self‐monitoring blood glucose (Al‐Qazaz, Hassali, Shafie, Sulaiman, & Sundram, ; Barbara & Krass, ; Ong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This means that when adults with T2DM have more diabetes knowledge, they are more likely to perform DSM in better ways for their health. This findings is consistent with findings from previous studies (Asmamaw et al., 2015; Kueh et al., 2015; van der Heide et al., 2014; Yang et al., 2016) and SCT (Bandura, 2004). To enhance the likelihood of DSM being practised among adults with T2DM in Vietnam, healthcare professionals need to advise their clients of the importance of monitoring their blood glucose levels and the meaning of A1C (Yang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%